Morphological variations of epiphytic Ficus deltoidea (Moraceae) and its agaonid pollinators, Blastophaga spp. - Noor Nasuha Abd Aziz; Abd Ghani Idris; Nur ‘Aliyaa Nizam; Nur Badrina Mohammad Naser; Malissa Mohamed; Siti Khairiyah Mohd Hatta (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The interaction between fig trees (Ficus) and their fig wasp pollinators (Agaonidae) is usually described as obligate mutualism. Ficus deltoidea (Moraceae) is distributed across southern Southeast Asia. Currently, F. deltoidea is regarded as only one species with 13 recognised varieties, and seven of them are native to Peninsular Malaysia. In this study, the morphological variation and relationship between epiphytic F. deltoidea var. angustifolia, var. deltoidea, and var. trengganuensis and their pollinating fig wasp in selected oil palm plantations from January 2017 to September 2017 were investigated. The ostiole diameter, gall width, and thickness of fig wall as well as fig wasp morphology were measured using image analyser. The female fig wasp associated with var. trengganuensis recorded the biggest value for wing length, mandible length, hind tibia length, and overall body length, whereas fig wasp associated with var. deltoidea recorded the highest value for head length, wing width, and ovipositor length. Fig wasp associated with var. angustifolia recorded the smallest value for all morphological parameters measured. Similarly, the male fig wasp associated with var. trengganuensis recorded the biggest value for mandible length, hind tibia length, and overall body length. There was a significant relationship between mandible size of male fig wasps and fig wall thickness (F=15.92, P<0.05), female fig wasp head width and ostiole diameter (F=9.02, P<0.05), and the male and female fig wasp with gall size (male: F=164.34, P<0.05; female: F=47.39, P<0.05) across the varieties. The results from this research explain that the morphological adaptations towards the structure of the figs occurred in the fig wasp’s evolution. The mutualism between the fig and fig wasp is also extremely specific across varieties in which even the same species of fig tree can have different pollinating fig wasps associated with different varieties.